One pot synthesis of Fe3O4/MnO2 core–shell structured nanocomposites and their application as microwave absorbers. Issue 31 (8th April 2015) - Liu, Xianguo; Wu, Niandu; Cui, Caiyun; Bi, Nannan; Sun, Yuping
<x xml:space="preserve">Abstract</x> Fe3O4/MnO2 core–shell structured nanocomposites have been synthesized by a one-pot approach at ambient temperature and pressure.